Exploring Alternative Approaches for Presenting Evaluation Results. (December 2013) - Johnson, Jeremiah; Hall, Jori; Greene, Jennifer C.; Ahn, Jeehae
Evaluators have an obligation to present clearly the results of their evaluative efforts. Traditionally, such presentations showcase formal written and oral reports, with dispassionate language and graphs, tables, quotes, and vignettes. These traditional forms do not reach all audiences nor are they likely to include the most powerful presentation possibilities. In this article, we share our use of alternative presentation formats, undertaken to increase the utility, appeal, and salience of our work. We offer a conceptual rationale for the use of "alternative representational forms" and describe the context for our use of alternative formats, which involved evaluations of various science, technology, engineering, and mathematics (STEM) educational programs. We present four examples, featuring visual display, performance, multiple program theories, and poetry. The article concludes with reflections on the future of alternative presentation approaches.